The Healthy Baby Flipbook: piloting home-based counseling for refugee mothers to improve infant feeding and water, sanitation, and hygiene (WASH) practices. Issue 1 (1st January 2019) - Hashmi, Ahmar; Carrara, Verena I.; Nyein, Paw Bay; Darakamon, Mu Chae; Charunwatthana, Prakaykaew; McGready, Rose
ABSTRACT: Problems in growth and undernutrition manifest in early infancy, with suboptimal breastfeeding and inadequate complementary feeding remaining strong risk factors for chronic undernutrition in infants. No published studies exist on educational interventions to improve infant feeding practices among refugees or displaced persons in low and middle-income (LMIC) settings. The objective of this study was to create and pilot educational materials for home-based counseling of refugee mothers along the Thailand–Myanmar border to improve appropriate infant feeding and water, sanitation, and hygiene (WASH) behaviors. Mothers of infants received counseling on appropriate infant feeding and WASH practices on a monthly basis for a total of six months from infant age three months until nine months. Educational materials were designed to feature a basic script for health workers and photos of locally available, appropriate foods. Of the 20 mothers participating in this pilot, infant feeding and WASH behaviors improved within 1 to 2 months of the first visit, including exclusive breastfeeding, minimum acceptable diet, and safe disposal of infant stool. This pilot demonstrates improvement in maternal infant feeding and WASH practices in a small set of refugee mothers, providing evidence for counseling measures to improve infant health in vulnerable populations. Trial registration: ClinicalTrials.gov identifier: NCT00840502.